A Comprehensive Review on AISI 4340 Hardened Steel: Emphasis on Industry Implemented Machining Settings, Implications, and Statistical Analysis - Panda, Amlana; Bag, Rabinarayan; Sahoo, Ashok Kumar; Kumar, Ramanuj (International Journal of Integrated Engineering, 2020)
Turning of hardened AISI 4340 steel is regarded as one of the demanding challenges in machining sectors where precision tolerances are essential for automobile parts. The AISI 4340 steel is broadly utilized in forged steel automotive crankshafts systems, hydraulic forged and additional machine tool purposes because of their improved characteristics.  Moreover, one of the keys confronts in the machining of hard 4340 steel is the comparatively deprived machining behavior that reduces the functionality of the material and further leads to component  rejection at the final inspection stage. In addition, accelerated tool wear necessitates for repeated changing of cutting tool that results in higher machining and tooling costs. This comprehensive review aimed to present in-depth features on the development of machining performances using various cutting tools. This review focus is to provide a broad perceptive of the role of controllable variables during machining of hardened steel. This review analysis examines the response variables and its advantages on chip morphology and heat generation. The comprehensive overview of machining settings, key machinability indicators and statistical analysis for AISI 4340 steel has been presented. This overview will provide academic, industrial and scientific communities with benefits and shortcomings through improved conceptual understanding towards further research and development.